2007
DOI: 10.1158/1078-0432.ccr-07-0816
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine Up-regulates S100A2 Expression and Synergizes with IFN-γ to Kill Uveal Melanoma Cells

Abstract: Purpose: Metastatic uveal melanoma is resistant to conventional chemotherapy and immunotherapy. In this study, we investigated the responsiveness of uveal melanoma cell lines to IFNs and the hypomethylating agent decitabine. Experimental Design: The uveal melanoma cell lines 92-1, UW-1, OCM-1, and MKT-BR were exposed to varying concentrations of IFN-a, IFN-g, and decitabine, alone and in combination. The effects of decitabine on gene expression were examined using DNA microarray analysis. Results: We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…We recently confirmed this observation using a panel of 40 stage III and stage IV melanoma tissue samples and we showed a significant reduction in S100A2 mRNA level in both stage III and stage IV compared to the control samples (Leclerc, Heizmann, and Vetter 2009). A role of S100A2 in uveal melanoma was also suggested by a recent study where cotreatment of uveal melanoma cells with decitabine and cell death inducing interferon-γ resulted in a dose-dependent increase in S100A2 expression, both at the transcription and protein level (Gollob and Sciambi 2007). As mentioned earlier, S100A2 locates in the nucleus where its most evident target appears to be p53.…”
Section: S100a2supporting
confidence: 63%
“…We recently confirmed this observation using a panel of 40 stage III and stage IV melanoma tissue samples and we showed a significant reduction in S100A2 mRNA level in both stage III and stage IV compared to the control samples (Leclerc, Heizmann, and Vetter 2009). A role of S100A2 in uveal melanoma was also suggested by a recent study where cotreatment of uveal melanoma cells with decitabine and cell death inducing interferon-γ resulted in a dose-dependent increase in S100A2 expression, both at the transcription and protein level (Gollob and Sciambi 2007). As mentioned earlier, S100A2 locates in the nucleus where its most evident target appears to be p53.…”
Section: S100a2supporting
confidence: 63%
“…Furthermore, a demethylating agent decitabine has been shown to sensitize melanoma cell lines to the cytotoxic effects of IFNs by inducing the expression of proapoptotic and growth-inhibitory genes. 107 The anti-apoptotic members of the Bcl -2 family are potential targets for immunosensitizing drugs. Bcl -2 is also upregulated in many cancer cells, and inactivating its function may result in a proapoptotic cancer cell inflammatory milieu facilitating cytotoxic activity of vaccine-induced immune cells.…”
Section: Small Moleculesmentioning
confidence: 99%
“…A major disadvantage of 5-azacytidine and 5-aza-2'-deoxycytidine is their instability in neutral aqueous solution and poor pharmacokinetic profile, although 5,6-dihydro-5-azacytidine and 5-fluoro-2'-deoxycytidine have demonstrated high toxicity in several preclinical studies. Another example was a phase 1 study, which showed that decitabine caused grade 4 neutropenia in most interleukin-2 inmelanoma and renal cell carcinoma patients (Gollob and Sciambi 2007). Myelosuppression was also the predominant toxicity observed in a study combining decitabine with carboplatin (Appleton et al 2007).…”
Section: Limitationsmentioning
confidence: 99%